Use of off-label drugs in neonatal intensive care - Andrea Sucasas Alonso; Alejandro Avila-Alvarez; Marina Combarro Eiriz; Cristina Martínez Roca; Pedro Yáñez Gómez; Alejandra Codias López; Jose Luis Fernández Trisac; Sonia Pértega Díaz (Elsevier, 2019)
Objective: To evaluate the prevalence of non-approved prescriptions (off-label and unlicensed) in a neonatal intensive care unit (NICU), and to describe factors of the neonate associated with its use. Materials and methods: Observational prospective study in a level III NICU during a 6-month period. Every prescription was analysed using the summary of product characteristics as a reference. A sequential algorithm was used to create a classification of prescriptions based on current status: approved, unlicensed, off-label (by age, route of administration, dosage, or indication). Results: The study included 84 patients and 564 prescriptions. A total of 127 (22.5%) prescriptions were considered off-label, and 45 (8%) were considered unlicensed. More than half (59.5%) of the patients received at least one of these drugs, and this increases to 100% among very preterm neonates and surgical patients (P < .001). A positive linear correlation was found between duration of NICU stay and the number of off-label prescriptions (correlation coefficient 0.6; P < .001). Conclusions: Non-licensed drugs are frequently prescribed in NICU, especially in the most vulnerable patients. Our results show the need to move forward on clinical research in order to homogenise the existing data about neonatology drugs, with the aim of making an efficient and safe prescription. Resumen: Objetivo: Evaluar la prevalencia de prescripciones en condiciones no autorizadas (off-label y unlicensed) en una Unidad de Cuidados Intensivos Neonatales (UCIN) y definir qué características de los neonatos se asocian a un mayor uso de fármacos en estas condiciones. Material y métodos: Estudio observacional prospectivo en una UCIN nivel III-C durante un periodo de 6 meses. Se evaluó la condición de uso de cada fármaco, tomando como referencia su ficha técnica. Se utilizó un algoritmo secuencial para la clasificación de las prescripciones en: aprobadas, unlicensed u off-label (por edad, por indicación, por vía de administración, y por dosis). Resultados: Se incluyeron 84 pacientes y 564 prescripciones. Un total de 127 prescripciones fueron consideradas off-label y 45 unlicensed; lo cual supuso el 22,5% y el 8% del total, respectivamente. El 59,5% de los pacientes recibieron al menos un fármaco en una de estas condiciones, ascendiendo este porcentaje al 100% en los grandes prematuros y en los pacientes quirúrgicos (p < 0,001). Se encontró una correlación lineal positiva entre la estancia en UCIN y el número de prescripciones off-label (coeficiente de correlación 0,6 p< 0,001). Conclusiones: La prescripción de fármacos en condiciones no autorizadas es habitual en UCIN, siendo especialmente frecuente en los pacientes con mayor vulnerabilidad. Estos resultados ponen de manifiesto la necesidad de avanzar en la investigación y homogeneizar la información existente sobre los fármacos en neonatología, con el objetivo de realizar una prescripción eficaz y segura.